DEIXIS TYPES IN “CHEF KICKS OUT HOMELESS CUSTOMER” SHORT MOVIE - Icha Sartika; Ambalegin Ambalegin (IdeBahasa, 2022)
This study aimed at identifying the use of deixis in “Chef Kicks out Homeless Customer” short movie by Dhar Mann. Moreover, this research concern about the type of deixis. In this research, qualitative descriptive is a research method used by the researchers. Data source in this study is “Chef Kicks out Homeless Customer” short film. The data were collected through observational method and non-participatory technique. Analyzing the data was done by using the pragmatic identity method and pragmatic competence-in-equalizing. The results of this study found the type of deixis, namely personal deixis, spatial deixis, and temporal deixis by using (Yule, 1996). Based on the results, there were 83 utterances of deixis by the main character in the short film. There were 70 utterances of person deixis found in the short movie. In addition, 10 utterances showed spatial deixis and 3 utterances referred to temporal deixis. The use of person deixis was found to be the most dominant deixis type in Chef Kicks out Homeless Customer short movie.